LncRNA HOTAIR is a novel endothelial mechanosensitive gene - da Silva, Rodrigo A. [UNESP]; Ferreira, Marcel Rodrigues [UNESP]; Gomes, Anderson Moreira [UNESP]; Zambuzzi, Willian F. [UNESP] (Wiley, 2020)
To better address whether the long noncoding RNAs (lncRNAs) HOTAIR and HOTTIP are mechanosensitive genes, they were investigated in differentially challenged endothelial cells with respect to a circuit of tensional forces, considering the performance of both arterial and venous endothelial cells. We subjected arterial- and venous-obtained endothelial cells to a circuit of tensional forces within a shear stress model in vitro. Real-time quantitative polymerase chain reaction analysis indicated that microRNA (miRNA)-related processing machinery is significantly required in shear stressed arterial endothelial cell metabolism, which orchestrates miRNA (small noncoding RNA) involvement, and their involvement suggests lncRNA involvement. Of lncRNAs HOTAIR and HOTTIP, only HOTAIR was mechanosensitive considering both arterial and venous endothelial cells, presenting a positive correlation between methylation signature and gene expression. Thereafter, using bioinformatics tools, lncRNA HOTAIR was predicted to modulate miRNA185, miRNA-21, and miRNA23b downregulation. We compared the values of gene expression with a Pearson's correlation test, and expected correlations were observed for miRNA185 (r = 0.8664), miRNA-21 (r = 0.8605), and miRNA23b (0.9128). Taken together, these findings clearly show that lncRNA HOTAIR responds to the shear stress and emerges as a novel mechanosensitive gene in endothelial cells. Altogether, this understanding of mechanosensitive transcriptional and posttranscriptional control involving HOTAIR can also lead to new forms of therapeutic intervention for various diseases, as well as new strategies for tissue engineering and regenerative medicine.
Keywords: epigenetics; HOTAIR; lncRNA; mechanosensitive; miRNA; shear stress